Cytotoxicity and Alkaline Phosphatase Activity of Curcumin, Aloin and MTA on Human Dental Pulp Cells - Dilara Dinc; Mehmet F. Seyhan; Oya Aktoren (Wolters Kluwer Medknow Publications, 2024)
Aim The objective of this in-vitro study was to assess the cytotoxicity and alkaline phosphatase (ALP) activity of curcumin and aloin extracted from Curcuma longa and Aloe vera, and mineral trioxide aggregate (MTA) on human dental pulp stem cells. Methods Human dental pulp stem cells (Lonza Group, Switzerland), curcumin (Sigma-Aldrich, USA), aloin (Sigma-Aldrich, USA), and ProRoot MTA (Dentsply, USA) were used in the study. 2.5-6.75-12.5-25-50 μg/ml of curcumin and aloin, 25%-50%-75%-100% of MTA were prepared; pulp cells unincubated with a material were assessed as controls. Cytotoxicity of all doses/concentrations of materials was analysed on days of 1, 2, 3, and 7 by WST-1 test. 2.5-6.75 μg/ml of curcumin and aloin, 25%-50% of MTA incubated with cells for 7-14 days were evaluated for ALP activity by ELISA test. Data was statistically analysed by One Way ANOVA, Tukey, and Sidak tests at GraphPad Prism 6. Results The findings have shown that 2.5 μg/ml of curcumin, all doses of aloin, 25% and 50% of MTA increased cell proliferation significantly on day 1 (P < 0.05). Curcumin, aloin, and MTA decreased the cell viability as dose/concentration and exposure time increased. All materials have shown no significant increases in ALP activity (P > 0.05) on 7 and 14 days. Conclusion Data of this study revealed that 2.5 - 6.75 μg/ml of curcumin/aloin, 25%-50% of MTA have promoted cell viability and proliferation of human dental pulp cells; and none of the materials have significantly increased the ALP activity at 7-14 days.